Persepsi dan Pemahaman Pelaku Usaha Terhadap Berlakunya Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah di Kota Bandung - Kasir (Jurnal Riset Bisnis dan Investasi, 2020)
The purpose of this study was to determine the perception and understanding of MSME centers business on the application of SAK EMKM starting Januari 1, 2018 at the MSME Business Center in Bandung. In this study the data used are primary data, that is data obtained directly from the object under study. Data obtained through questionnaires to several MSME business center operastors int the city of Bandung. Sampling was carried out using the Sloving formula, resulting in 336 MSME respondents. The regression model used in this study to use Multiple Regression Analysis. The results of this study by t test (partial) showed that the perception of MSME actors did not effect the implementation of SAK EMKM and the understanding of MSME actors influenced the implementation of SAK EMKM. While the F test (simultaneous) showed that the perception and understanding of MSME actors influence the implementation of SAK EMKM.